Non-Inflammasome Forming NLRs in Inflammation and Tumorigenesis - Allen, Irving Coy (Frontiers in Immunology, 2014)
Aberrant inflammation is an enabling characteristic of tumorigenesis. Thus, signaling cascades that alter inflammatory activation and resolution are of specific relevance to disease pathogenesis. Pattern recognition receptors (PRRs) are essential mediators of the host immune response and have emerged as critical elements affecting multiple facets of tumor pathobiology. The nucleotide-binding domain and leucine-rich repeat containing (NLR) proteins are intracellular PRRs that sense microbial and non-microbial products. Members of the NLR family can be divided into functional subgroups based on their ability to either positively or negatively regulate the host immune response. Recent studies have identified a novel subgroup of non-inflammasome forming NLRs that negatively regulate diverse biological pathways associated with both inflammation and tumorigenesis. Understanding the mechanisms underlying the function of these unique NLRs will assist in the rationale design of future therapeutic strategies targeting a wide spectrum of inflammatory diseases and cancer. Here, we will discuss recent findings associated with this novel NLR subgroup and mechanisms by which these PRRs may function to alter cancer pathogenesis.